An invisible minority: Romany Gypsies and the question of whiteness. Issue 1 (June 2019) - Webb, Emily
Abstract : The aim of this paper is to explore the uncertain whiteness of Britain's Romany Gypsies. Their "white, but not quite" status means that Romany Gypsies are simultaneously accepted and rejected from the category of "white British." This paper will focus on the many ways in which Romany Gypsies become identifiable as "white others" despite being phenotypically unmarked by race. It seeks to understand the impact of whiteness upon Romany Gypsy claims to minorityhood, in relation to multiculturalism and antiracism, by exploring their competing claims to sameness and difference with white Britons. The paper will argue that whiteness renders Britain's Romany Gypsies an invisible minority who, by nature of their skin colour, often go unrecognized in narratives of racial and ethnic discrimination.